Deposition of carbon nanotubes in commonly used sample filter media - B.D. Smith; S.B.H. Bach (Global Journal of Environmental Science and Management)
There is no single standard technique or methodology to characterize the size, structure, number, and chemical composition of airborne carbon nanotubes.  Existing analytical instruments and analytical techniques for evaluating nanoparticle concentrations cannot simultaneously provide morphology, state of agglomeration, surface area, mass, size distribution and chemical composition data critical to making occupational health assessments.  This research utilized scanning electron microscopy and thermogravimetric analysis to assess the morphology and mass of carbon nanotubes collected using various commercial sample filters.  It illustrated carbon nanotube agglomeration, deposition and distribution in commonly used sample filter media.  It also illustrated that a sufficient mass for carbon nanotube analysis by thermogravimetric analysis is uncommon under most current research and production uses of carbon nanotubes.  Individual carbon nanotubes were found to readily agglomerate with diameters ranging from 1 – 63 µm. They were collected at the face of or within the filter.  They were not evenly distributed across the face of the filters.